2022
DOI: 10.3389/fphar.2021.794453
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Attitude, and Confidence of Physicians About Antimicrobial Resistance and Antimicrobial Prescribing Among COVID-19 Patients: A Cross-Sectional Study From Punjab, Pakistan

Abstract: Background: Patients with coronavirus disease 2019 (COVID-19) could experience multiple coinfections, and judicial antimicrobials, including antibiotics, is paramount to treat these coinfections. This study evaluated physicians’ perception, attitude, and confidence about antimicrobial resistance (AMR) and antimicrobial prescribing in patients with COVID-19.Methods: A self-administered and validated online questionnaire comprised of six sections was disseminated among physicians working in public sector hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Clinicians’ attitudes towards antibiotic prescribing in COVID-19 patients may have also been influenced by the introduction of treatment guidelines for COVID-19 patients (such as those issued by the WHO [ 13 ] and UK NICE [ 14 ]), which advised against antibiotic use in mild COVID-19 patients and in moderately ill patients without a suspected or confirmed bacterial infection. A cross-sectional study in Pakistan [ 23 ] that evaluated physicians’ perceptions, attitudes and confidence about AMR and antibiotic prescribing in COVID-19 patients from Apr to May 2021, found that most physicians had a high awareness of AMR during the pandemic and were confident about antibiotic prescribing in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians’ attitudes towards antibiotic prescribing in COVID-19 patients may have also been influenced by the introduction of treatment guidelines for COVID-19 patients (such as those issued by the WHO [ 13 ] and UK NICE [ 14 ]), which advised against antibiotic use in mild COVID-19 patients and in moderately ill patients without a suspected or confirmed bacterial infection. A cross-sectional study in Pakistan [ 23 ] that evaluated physicians’ perceptions, attitudes and confidence about AMR and antibiotic prescribing in COVID-19 patients from Apr to May 2021, found that most physicians had a high awareness of AMR during the pandemic and were confident about antibiotic prescribing in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The improper use of antibiotics in patients without a bacterial infection might also cause a cytokine-mediated over-activation of the immune system and a septic shock-like phenomenon, thus worsening the hyper-inflammation stimulated by COVID-19 (Wypych et al, 2018, McAleer et al, 2018, Marsland et al, 2015. Another possible explanation might be related to patients' and clinicians' risk perception and differences in disease management over time (Arefi et al, 2022, Hayat et al, 2022. In fact, during the early phases of the pandemic the intensity of COVID-19 patients care was mainly based on empirical evidence such as disease severity, clinical symptoms, and risk of disease progression (Jampani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The study instrument used in our survey was developed from relevant studies conducted among health care professionals. [37][38][39][40] Various concurrent activities were subsequently undertaken to ensure internal consistency, validity and robustness of the questionnaire used in the principal study. Firstly, the initial study questionnaire was carefully reviewed by a multidisciplinary team comprising a practicing MSN (Master of Science in nursing) nurse and two academic staff with PhDs in pharmacy to determine the content validity of the questionnaire.…”
Section: Study Instrumentmentioning
confidence: 99%